T67. TRAUMA IN AFFECTIVE AND NONAFFECTIVE PSYCHOSIS: ASSOCIATIONS AND DISSOCIATIONS WITH COGNITIVE FUNCTIONING IN CHILDHOOD AND ADULTHOOD. (18th May 2020) - Mollon, Josephine; Knowles, Emma; Mathias, Samuel; Rodrigue, Amanda; Koenis, Marinka; Pearlson, Godfrey; Glahn, David
Abstract: Background: Childhood trauma and cognitive impairment are important risk factors for psychotic disorders. However, the relationship between trauma and psychosis throughout the lifespan, as well as between lifetime trauma and cognitive functioning, remain unclear. Methods: Using data from a case-control study of African-American adults with psychotic disorders, we examined childhood and adult trauma, as well as their interaction with cognitive functioning, in adults with affective psychotic disorders (n=101), nonaffective psychotic disorders (n=109), non-psychotic psychiatric disorders (n=105), compared to controls (n=211). Childhood trauma was measured using the Childhood Trauma Questionnaire (CTQ), which produces dimensional measures of physical neglect, emotional neglect, physical abuse, emotional abuse, and sexual abuse. Adult trauma was measured using the Trauma History Questionnaire (THQ), which ascertains the presence of death-, and personal-related traumas throughout adulthood. Cognitive functioning was measured using a comprehensive computerized battery ('Charlie', https://github.com/sammosummo/Charlie ). Results: All three psychiatric groups showed greater childhood trauma compared to controls, but the affective psychosis group showed the most trauma (Cohen d=0.97–1.29, p<0.001), followed by the nonaffective psychosis group (d=0.54–0.72, p<0.001), and then the non-psychotic group (d=0.05–0.16, p<0.04). Despite the fact that childhood trauma was significantly associated with adult trauma (OR=0.67–2.08, p<0.002), only the affective psychosis group showed a significantly increased likelihood of experiencing both death- and personal-related traumas in adulthood (OR=0.86–2.14, p<0.01), while the nonaffective psychosis group showed an increased likelihood of experiencing personal-related traumas (OR=1.00, p=0.003). Significant childhood-trauma-by-group interactions on cognitive functioning showed that greater childhood neglect was associated with better performance in the affective psychosis group on measures of processing speed (d=0.52, p=0.011), social processing (d=0.57, p=0.020), and executive functioning (d=0.50–0.71, p<0.020). A similar pattern emerged in the affective psychosis group with both death- and personal-related adult traumas on measures of processing speed (d=0.67–0.74, p<0.010), memory (d=0.67–0.68, p<0.014), and emotional processing (d=0.79, p=0.008). In the domain of complex reasoning, on the other hand, increased childhood sexual abuse in the affective psychosis group, and personal-related adult traumas in the psychosis group, showed a deleterious effect (d=–0.44, p=0.025; d=–0.65, p=0.010). Discussion: Individuals with psychotic disorders, especially affective psychoses, experienced more childhood and adult trauma than controls, and also individuals with non-psychotic psychiatric disorders. However, both childhood neglect and adult trauma were associated with better cognitive functioning in the affective psychosis group. One explanation for this seemingly paradoxical finding may be that traumatic experiences in childhood and adulthood lead to increased cognitive vulnerability, as typically seen in psychotic disorders. Thus, individuals who experience more lifetime trauma may follow a different pathway to psychosis, involving less neurodevelopmental impairment, but greater environmental stress, leading to more affective, rather than nonaffective, manifestations of psychosis.